Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1096/fj.08-121657
|View full text |Cite
|
Sign up to set email alerts
|

γ‐Secretase‐dependent cleavage of amyloid precursor protein regulates osteoblast behavior

Abstract: gamma-Secretase cleaves amyloid precursor protein (APP) to generate amyloid-beta (Abeta) peptides, which aggregate in the brain in Alzheimer's disease (AD). gamma-Secretase also cleaves molecules that regulate osteoblast activity, such as Notch and ephrinB2. However, the role of APP in bone is unknown. In this study, the expression, cleavage, and function of APP were investigated during osteogenesis in vitro and in vivo. Expression of all gamma-secretase subunits was confirmed in human primary osteoprogenitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 66 publications
(79 reference statements)
2
9
0
Order By: Relevance
“…(A) Mitochondrial morphology in human papillary thyroid cancers (PTCs) with low or high kinase suppressor of RAS1 (KSR1) expression (original magnification, pathway is able to promote Notch signaling activation by g-secretase complex-dependent proteolysis (Tremblay et al 2013). Although we could not demonstrate g-secretase complex activity using the g-secretase peptide cleavage assay (Farmery et al 2003, McLeod et al 2009), we observed an increase in the level of the transmembrane/intracellular region (NTM) of NOTCH1 upon BRAFV600E transfection, which is consistent with the results of the previous study. Remarkably, knockdown of KSR1 by siRNA abrogated NOTCH1 activation by BRAFV600E, suggesting that KSR1 is required for BRAFV600E-induced Notch activation.…”
Section: Discussionsupporting
confidence: 91%
“…(A) Mitochondrial morphology in human papillary thyroid cancers (PTCs) with low or high kinase suppressor of RAS1 (KSR1) expression (original magnification, pathway is able to promote Notch signaling activation by g-secretase complex-dependent proteolysis (Tremblay et al 2013). Although we could not demonstrate g-secretase complex activity using the g-secretase peptide cleavage assay (Farmery et al 2003, McLeod et al 2009), we observed an increase in the level of the transmembrane/intracellular region (NTM) of NOTCH1 upon BRAFV600E transfection, which is consistent with the results of the previous study. Remarkably, knockdown of KSR1 by siRNA abrogated NOTCH1 activation by BRAFV600E, suggesting that KSR1 is required for BRAFV600E-induced Notch activation.…”
Section: Discussionsupporting
confidence: 91%
“…APP is expressed ubiquitously, and Abeta is a normal catabolic product of APP metabolism in most cells, including bone cells. The proteases, beta- and gamma-secretases, that cleave APP for the generation of Abeta are also expressed in bone cells (73). Transgenic mice expressing mutant APP exhibits reduced bone volume (73), implicating a function of mutant APP in bone remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to standard γ-secretase inhibitors, BNC-1 did not significantly alter levels of PS-2 or significantly impact Notch-1 cleavage (Table 1). To verify BNC-1 targets PS-1 expression and is not simply a pan γ-secretase inhibitor subject to the same adverse effects as existing γ-secretase inhibitors, we carried out γ-secretase inhibition assays as previously described [50] using an internally quenched peptide substrate consisting of the C-terminal -AβPP amino acid sequence cleaved by γ-secretase (NMA-Gly-Gly-Val-Val-Ile-Ala-Thr-Val-Lys(DNP)-D-Arg-D-Arg-D-Arg-NH 2 ; Calbiochem) and membrane fractions containing γ-secretase prepared from 5XFAD transgenic mice overexpressing three human APP and two PS1 familial AD (FAD) mutations. Results of the assay showed BNC-1 did not significantly decrease γ-secretase activity up to 1 μM concentrations, whereas treatment with 100 nM L-685,458 (Tocris) a well characterized potent and selective γ-secretase inhibitor led to 45% inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…To verify BNC-1 targets PS-1 expression and is not simply a pan γ-secretase inhibitor, we carried out γ-secretase inhibition assays as previously described [50] using an internally quenched peptide substrate consisting of the C-terminal β-AβPP amino acid sequence cleaved by γ-secretase (NMA-Gly-Gly-Val-Val-Ile-Ala-Thr-Val-Lys (DNP)- D -Arg- D -Arg- D -Arg-NH 2 ; Calbiochem) and membrane fractions containing γ-secretase prepared from 5XFAD transgenic mice overexpressing three human APP and two PS1 FAD mutations.…”
Section: Methodsmentioning
confidence: 99%